HRM Practices in Indonesia: the Contributing Power of Embeddedness and Support - Martono, S; Putri, Vini Wiratno (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2018)
This study aims to test the effect of HRM practices on the employees’ task performance and how the correlation is mediated by the variables of job embeddedness and perceived organizational support. The methods of data collection employed observation, questionnaire online and offline, and interview. Sampling uses the survey method, with the number of respondents 480 (response rate 87.27%) academics in Indonesia. The analysis of Structural Equation Modeling (SEM) with Warp PLS program was used to test the hypothesis. The result of this study shows that the supported HRM practices affect employee performance, job embeddedness and perceived organizational support. Employee performance is also directly affected by job embeddedness and perceived organizational support. Based on the result, there is an effect of HRM practices on the task performance, the better HRM practices are, the more employees’ task performance will improve. Job embeddedness and perceived organizational support are also affected by HRM practices. In addition, this study also proves that job embeddedness and perceived organizational support can also improve employees’ task performance. Besides affecting directly, job embeddedness and perceived organizational support have a role as mediating variables in the HRM practices on performance. The result of this study provides an understanding that good HRM practices are crucial to be applied not only in the profitable organization but also in the universities. This study provides a description of the importance of good HRM practices to be implemented in the universities. Furthermore, it is necessary to continue studying the roles of human resources practices with the larger sample.